LED based wavelength division multiplexed 10 Gb/s Visible Light Communications - Chun, H; Rajbhandari, S; Faulkner, G; Tsonev, D; Xie, E; McKendry, J; Gu, E; Dawson, M; O'Brien, D; Haas, H (Institute of Electrical and Electronics Engineers, 2016)
LED based Visible Light Communications can provide high data rates to users. This can be further increased by the use of wavelength division multiplexing, using the different colours required to generate white light to transmit different data streams. In this paper a trichromatic approach is described, and the influence of colour combination on achievable data rate is analysed. A demonstration of LED based communications which achieves a data rate of >10 Gb/s by using a rate adaptive orthogonal-frequency-division-multiplexing scheme is also reported.